Avaliação da qualidade de vida da população idosa numa estância turística do interior do Estado de São Paulo: aplicação da escala de Flanagan - Corrente, José Eduardo [UNESP]; Machado, Adriana Braga de Castro [UNESP] (My University, 2010)
The increase in life expectancy worldwide and particularly in developing countries such as Brazil has led to an intense demand for studies and analyses in order to better define public policies and improve the quality of life of elderly people. Objective: evaluate the quality of life of elderly people in a tourist resort in the interior of São Paulo State. Methods: Flanagan`s Quality of Life Scale was applied to a sample of 365 elderly persons assisted by the public health care network, by means of household interviews at a tourist resort in the interior of São Paulo state, Brazil. The sample, obtained from an unknown prevalence, was stratified by age. Results: Among the 365 elderly persons interviewed, the mean age was 70.26 years (SD 6.37 years); most of them were females (56.01%); 56.29% were married; 88.52% were retired; 48.53% had attended school for fours years and 64.81% had an income of up to one minimum salary. As regards satisfaction about life in general, 93.69% reported to be satisfied. The application of Flanagan’s quality of life scale showed a Cronbach’s alpha value of 0.7660, thus indicating good efficacy for the instrument. Factorial analysis of the answers showed that elderly people valued the following items as quality of life: physical and material well-being, personal development and fulfillment, relationships with other people, and social and community activities, thus presenting some divergences with the domains proposed by Flanagan. Conclusion: Hence, in a general context, it is possible to state that the quality of life of elderly people can be considered good according to the Flanagan’s Quality of Life Scale, and taking into account its limitations. Additionally, the factors that mostly influenced general satisfaction about life were lack of opportunity to perform leisure activities, comfort in relation to one’s place of residence and financial conditions.

Atualmente, com o crescente aumento da expectativa de vida no mundo e em países em desenvolvimento como o Brasil, criou-se uma intensa demanda por estudos e análises para uma otimização de políticas públicas e melhora na qualidade de vida do idoso. Objetivo: avaliar a qualidade de vida de idosos residentes numa estância turística do interior do Estado de São Paulo. Metodologia: foi aplicada a Escala de Qualidade de Vida de Flanagan a uma amostra de 365 idosos atendidos na rede pública de saúde, através de entrevistas domiciliares em uma estância turística no interior do Estado de São Paulo, Brasil. A amostra foi obtida a partir de uma prevalência desconhecida e estratificada por idade. Resultados: Dos 365 idosos entrevistados, a idade média foi de 70,26 anos com um desvio padrão de 6,37 anos, a maioria era do sexo feminino (56,01%), 56,29 eram casados, 88,52% eram aposentados, 48,53% possuíam o ensino básico e 64,81% tinham renda de até um salário mínimo. Com relação à satisfação com a vida em geral, 93,69% declaram estarem satisfeitos. A aplicação da escala de qualidade de vida de Flanagan apresentou um valor de alpha de Cronbach de 0,7660, indicando uma boa eficiência do instrumento. A análise fatorial das respostas obtidas na aplicação da escala mostrou que os idosos valorizam, como qualidade de vida, o bem estar físico e material, o desenvolvimento pessoal e a realização, relações com outras pessoas, atividades sociais e comunitárias, apontando algumas divergências com os domínios propostos por Flanagan. Conclusão: Desse modo, num contexto geral, pode-se afirmar que a qualidade de vida dos idosos pode ser considerada boa, de acordo com os resultados da Escala de Qualidade de Vida de Flanagan e de acordo com as suas limitações. Além disso, os fatores que mais influenciaram na satisfação da vida em geral foram não terem oportunidades para desempenhar atividades de lazer, conforto com o lugar onde moram e a situação financeira.
Quality of life assessment of an elderly population of a resort in the state of São Paulo: application of the Flanagan's scale
Keywords: Elderly; Elderly health; Quality of life; Factorial analysis; Idoso; Saúde do idoso; Qualidade de vida; Análise fatorial